2021
DOI: 10.21203/rs.3.rs-218217/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a Highly Predictive Survival Nomogram For Patients With Sepsis: A Retrospective Cohort Study

Abstract: Background: Sepsis is a critical illness common in intensive care units (ICUs) and emergency rooms worldwide and is associated with high morbidity and mortality. However, exisiting methods to predict mortality from sepsis, such as the Sequential Organ Failure Assessment (SOFA) score, are insufficient. This paper aimed to construct a nomogram for predicting the 30-, 60-, and 90-days mortality risks of patients with sepsis that is more accurate than the SOFA score alone. Methods: Data on sepsis patients were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In their study on post-traumatic patients with sepsis, Lu et al demonstrated that the predictive ability of a model based on clinical and biochemical markers that incorporated the albumin level (AUROC = 0.799) outperformed the SOFA score (AUROC = 0.698; p < 0.001). In another retrospective study on 5240 patients with sepsis, adding other laboratory parameters into the SOFA score improved ability to predict death in 30 days (AUROC = 0.681-0.766) [29,30]. A recent retrospective study on 725 patients with sepsis who were discharged from the hospital found that a serum albumin level of <2.5 mg/dL (odds ratio [OR] = 2.616) and a SOFA score of ≥2 (OR = 2.106) at discharge were independent prognostic factors for one-year mortality, indicating that these two variables may fit well in the prognostic assessment of patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…In their study on post-traumatic patients with sepsis, Lu et al demonstrated that the predictive ability of a model based on clinical and biochemical markers that incorporated the albumin level (AUROC = 0.799) outperformed the SOFA score (AUROC = 0.698; p < 0.001). In another retrospective study on 5240 patients with sepsis, adding other laboratory parameters into the SOFA score improved ability to predict death in 30 days (AUROC = 0.681-0.766) [29,30]. A recent retrospective study on 725 patients with sepsis who were discharged from the hospital found that a serum albumin level of <2.5 mg/dL (odds ratio [OR] = 2.616) and a SOFA score of ≥2 (OR = 2.106) at discharge were independent prognostic factors for one-year mortality, indicating that these two variables may fit well in the prognostic assessment of patients [31].…”
Section: Discussionmentioning
confidence: 99%